Linking big data for cardiovascular health surveillance – opportunities and challenges using the CANHEART cohort. (2018) - Chu, Anna; Hennessy, Deirdre; Johnston, Sharon; Udell, Jacob; Ko, Dennis; Khan, Anam; Jia, Jing; Tu, Jack
No abstract available